Cell wall and cytoskeletal contributions in single cell biomechanics of Nicotiana tabacum. (21st January 2022) - Ginsberg, Leah; McDonald, Robin; Lin, Qinchen; Hendrickx, Rodinde; Spigolon, Giada; Ravichandran, Guruswami; Daraio, Chiara; Roumeli, Eleftheria
Abstract: Studies on the mechanics of plant cells usually focus on understanding the effects of turgor pressure and properties of the cell wall (CW). While the functional roles of the underlying cytoskeleton have been studied, the extent to which it contributes to the mechanical properties of cells is not elucidated. Here, we study the contributions of the CW, microtubules (MTs) and actin filaments (AFs), in the mechanical properties of Nicotiana tabacum cells. We use a multiscale biomechanical assay comprised of atomic force microscopy and micro-indentation in solutions that (i) remove MTs and AFs and (ii) alter osmotic pressures in the cells. To compare measurements obtained by the two mechanical tests, we develop two generative statistical models to describe the cell's behaviour using one or both datasets. Our results illustrate that MTs and AFs contribute significantly to cell stiffness and dissipated energy, while confirming the dominant role of turgor pressure.